2019
DOI: 10.1073/pnas.1817147116
|View full text |Cite|
|
Sign up to set email alerts
|

Nanobody-based CAR T cells that target the tumor microenvironment inhibit the growth of solid tumors in immunocompetent mice

Abstract: Chimeric antigen receptor (CAR) T cell therapy has been successful in clinical trials against hematological cancers, but has experienced challenges in the treatment of solid tumors. One of the main difficulties lies in a paucity of tumor-specific targets that can serve as CAR recognition domains. We therefore focused on developing VHH-based, single-domain antibody (nanobody) CAR T cells that target aspects of the tumor microenvironment conserved across multiple cancer types. Many solid tumors evade immune reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
182
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(204 citation statements)
references
References 47 publications
(68 reference statements)
1
182
0
Order By: Relevance
“…The low immunogenicity of the nanobodies (17,18) should make any targeted agent poorly visible to the immune system, thereby reducing systemic toxicities. An example of such an application is presented in an accompanying paper (51), which describes incorporation of the NJB2 nanobody into CAR T cells to enhance their antitumor activity. The imaging of the EIIIB-KO mice and the detection of normal mouse cartilage by NJB2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The low immunogenicity of the nanobodies (17,18) should make any targeted agent poorly visible to the immune system, thereby reducing systemic toxicities. An example of such an application is presented in an accompanying paper (51), which describes incorporation of the NJB2 nanobody into CAR T cells to enhance their antitumor activity. The imaging of the EIIIB-KO mice and the detection of normal mouse cartilage by NJB2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…120 121 CAR T cells with anti-PD-L1 targeting have demonstrated cytotoxic activity in mice bearing melanoma and colon tumors. 122 In addition, CAR T cells have been developed with a switch receptor construct composed of extracellular PD-1 domains coupled to transmembrane and cytoplasmic CD28 signaling domains. 123 These CAR T cells have been shown to induce tumor regression in murine models of prostate cancer.…”
Section: Alternative Mechanisms Of Immune Modulation For T Lymphocytementioning
confidence: 99%
“…This approach may employ human scFvs for CAR construct design to improve the long-term survival of CAR-T cells, whereas a potential human anti-mouse antibody reaction may eliminate CAR-T cells that use a murine scFv for binding and lead to poor persistence. In recent years, efforts have been made to replace scFvs with nanobodies derived from camelids 241 , and preclinical studies have shown that nanobody-based CAR-T cells showed improved flexibility in antigen recognition and achieved comparable efficacy when treating different tumors 242,243 . CAR-T cells attack cells expressing the CAR-recognized antigens, which are always TAAs.…”
Section: Binding Domainmentioning
confidence: 99%